Germany’s Research Platform for Sustainable Process Metallurgy From Nano to Mega Scale Experiments - Friedrich, Bernd (JOM (1989), 2017)
Rheinisch-Westfalische Technische Hochschule (RWTH) Aachen University was founded in 1870 and, in 2007, was selected by the German Research Foundation as one of nine German Universities of Excellence. Advancement of non-ferrous metallurgy is the focus of the Institute for Process Metallurgy and Metal Recycling (IME) at RWTH. A key competency of IME is the continuous development of economic and resource-efficient processes for the treatment and revaluation of raw materials and wastes. Solutions need to be innovative, competitive, apply to industry's needs, and fulfill strict requirements for sustainability and zero-emission metallurgy. Work starts with thermochemical modeling and theoretical studies, as well as fundamental research, and extends to experimental large-scale test runs. IME's research is organized within five main areas to cover a broad range of proven, innovative metallurgical process technologies such as recycling-, slag-, vacuum-, hydro-, microwave-, electro-, aluminothermic- and nanometallurgy: 1. pyrometallurgy, 2. hydrometallurgy, 3. nanometallurgy, 4. vacuum metallurgy, and 5. molten salt electrolysis.